Composição coreográfica: reflexões sobre os modos de produzir dança de três coreógrafos amazonenses - Rodrigues, Igor Laborda (2023)
The choreographic composition in dance has its own line of thought, although it is a very common and traditionally used term, recently its concept has been expanded. Bearing this in mind, this scientific research has as its proposal the investigation into the ways of producing dance from the point of view of three Amazonian choreographers, with the objective of offering general lines an overview of the procedures for choreographic compositions, providing a singular vision regarding the their ways of doing, understanding, conceptualizing and encompassing processes of choreographic compositions of each research subject. This research is characterized as field research, and of a qualitative nature, being relevant for the academic public/artist and art lovers, since it enables a dialogue with those who observe it, revealing the understanding we have of the world in the way we see it. it or make it.